2000
DOI: 10.1099/00221287-146-5-1035
|View full text |Cite
|
Sign up to set email alerts
|

The Candida albicans antiporter gene CNH1 has a role in Na+ and H+ transport, salt tolerance, and morphogenesis The GenBank accession number for the sequence reported in this work is AF128238.

Abstract: The isolation and functional characterization of a Candida albicans Na M /H M antiporter gene, CNH1, is reported here. The gene encodes a protein of 840 amino acids that exhibits high levels of similarity in sequence, size, and structural and functional domains to a group of known Na M /H M antiporters of fungi. The CNH1 gene is able to functionally complement the salt-sensitivity of a Saccharomyces cerevisiae ena1 nha1 mutant, and mutations of two conserved aspartate residues to asparagines in the putative Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…et al, 2001b). Deletion of CNH1 leads to retardation of growth and a highly elongated morphology of cells, but it has little effect on the sensitivity of C. albicans cells to high concentrations of sodium and lithium (Soong et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…et al, 2001b). Deletion of CNH1 leads to retardation of growth and a highly elongated morphology of cells, but it has little effect on the sensitivity of C. albicans cells to high concentrations of sodium and lithium (Soong et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…, S. Potier and H. Sychrova! albicans strains, SC5314 (Soong et al, 2000) and MEN (Kinclova! et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cells have relatively high concentrations of K + and low concentrations of Na + , which are achieved by the coordinated functions of different transporters for cation influx and efflux. The NHA1 gene product has been described as a Na + /H + antiporter because it is involved in sodium tolerance and it has similarities to the Na + /H + antiporters sod2 of Schizosaccharomyces pombe (Jia et al, 1992), Z-Sod2 and Z-Sod22 of Zygosaccharomyces rouxii (Iwaki et al, 1998;Watanabe et al, 1995) and Cnh1 of Candida albicans (Soong et al, 2000). Nha1p has been shown to be involved in K + efflux through the plasma membrane, playing an important role during growth in a highpotassium environment (Bañ uelos et al, 1998;Kinclová et al, 2001).…”
mentioning
confidence: 99%
“…These residues are conserved in the antiporters of prokaryotes and of some lower eukaryotes, despite an overall low similarity in their primary sequences (28). The tandem of aspartyl residues identified in the Spsod2p study were shown to be vital for the function of the Z. rouxii Sod2 antiporter (Asp 265 -Asp 266 ) (31), and mutations of conserved aspartyl residues 266 and 267 to asparagine reduced the sodium transport activity also in C. albicans Cnh1p and S. cerevisiae Nha1p (17,26). Interestingly, in the case of ScNha1 (D266,267N) antiporter, the potassium efflux activity was not changed, and it was another aspartyl residue (Asp 241 ) whose mutation affected K ϩ extrusion (26).…”
Section: Namentioning
confidence: 99%
“…Genes encoding ScNha1p homologues have been cloned from six yeast species: Schizosaccharomyces pombe (12), Zygosaccharomyces rouxii (13)(14)(15), Pichia sorbithophila (16), Candida albicans (17,18), Candida tropicalis, and Hansenula anomala (19). The systematic genome sequencing of other yeast species revealed the existence of similar open reading frames in all of them (20)(21)(22).…”
Section: Namentioning
confidence: 99%